Gas pricing reform in India: will it transform the gas landscape? - Sen, A (Oxford Institute for Energy Studies, 2015)
In November 2014, India implemented an unprecedented reform of domestic gas pricing. Under the reform, India’s gas price (formerly controlled by the government at $4.20/MMBtu) became linked to a volume-weighted average of world gas prices – US Henry Hub, UK NBP, Alberta Gas Reference price, and the Russian domestic gas price. The price is to be reset every six months, based on a twelve month trailing average with a lag of one quarter.